Electronic Dictionaries - The Dictionary of Modern Arabic by Ahmed Mukhtar Omar as a model (Journal of Human Sciences, 2023)
The world recently witnessed the dominance of the technical side and a race towards digitization, and in the face of this development, the Arabic language caught up, which resulted in multiple scientific studies in the field of language computerization in order to modernize it The completion of electronic dictionaries is an urgent necessity imposed by the scientific development as part of it. It was crowned with a real achievement embodied on the ground that witnessed different types, then followed by the stage of evaluating those efforts aimed at bringing them to the desired level.